Institutional reorientation: the case of Universidade Aberta - Bento, P.; Sousa, H.; Almeida, M. (Economia Global e Gestão, 2012)
The goal of this study is to provide guidelines for the restructuring process of Universidade Aberta, which is the Portuguese distance learning university. The external and internal assessments were performed using multiple instruments, of which we highlight a survey with responses from over twenty countries. This survey was analyzed using advanced data mining methods along three dimensions: educational offer, target publics and operating model. The specific guidelines are based on the assumption of a certain status quo in the higher education sector.